IMF Staff Papers, Volume 48, Special Issue, Transition Economies, How Much Progress? - Haas, Richard; Havrylyshyn, Oleh.; Sahay, Ratna (Washington, D.C. : International Monetary Fund, 2002)
This chapter is the collection of eight papers on different aspects of the first 10 years of economic transition. Transition issues have appeared initially quite controversial. There have been controversies on the speed of reforms, privatization methods, the role and organization of government, the kind of financial system needed, et cetera Although these controversies often have been ideological, they also reflect to a large extent the initial ignorance and unpreparedness of the economics profession with respect to the large. Resident representatives in transforming economies have had a unique opportunity to witness and participate in one of the most interesting and challenging events of the economics profession in the past 50 years: the transformation of centrally planned economies into market-based systems. The job is intellectually fascinating, frequently extremely rewarding, occasionally frustrating, however, never boring. The decline in cash revenue in Russia has been the key macroeconomic policy failure of the transition. This paper argues that the fall in cash compliance emerged when money printing was replaced with a method of budget financing that did not, in the short run, compromise the government's goals of low inflation, a stable exchange rate, and low interest rates, but which ultimately has led the government into a low cash revenue trap.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet